Being Blind in a World of Multiple Perspectives: The Evaluator's Dilemma Between the Hope of Becoming a Team Player and the Fear of Becoming a Critical Friend with No Friends - Michele Tarsilla (The Evaluation Center at Western Michigan University, 2010)
Background: A large number of evaluation theorists have debated the issue of objectivity and bias in evaluation over the last five decades. In particular, the degree to which distance from the evaluand enhances the validity and reliability of evaluation findings has been a prominent topic of discussion. Purpose: This article has two primary objectives. First, it intends to present some of the positivist and post-positivist theories on distance that have dominated the evaluation discourse since the late 1960's, by also showing the limitations of their respective assumptions. Second, it describes a more recent evaluation theory on distance that is proving to help evaluators rapport with their evaluand more effectively, especially in the case of complex programs involving a large variety of stakeholders. Setting: Not applicable. Subjects: Not applicable. Research Design: Not applicable. Data Collection and Analysis: The paper is the result of both a desk review and a series of interviews with some major evaluation theorists aimed to compare and contrast some of the most relevant ideas on distance in evaluation expressed over the last five decades. Findings: The author shows that evaluators today are still facing the dilemma of whether they should seek proximity to or distance from the evaluand. However, the author identifies an increasingly popular evaluation approach (herewith referred as the pluralist approach as opposed to the niche approach) that promises to overcome the issue of distance in evaluation more successfully than any other earlier theory. The author dismisses the idea of absolute distance, predicated by both Scriven and Campbell. In doing so, he also shows that evaluators who are closer to the evaluand and the context contiguous to it tend to have a deeper understanding of the issues at stake and therefore enhance the overall quality of their evaluation. In addition, the author acknowledges that evaluators today have a new important role to play vis-à-vis their evaluand: mediating stakeholders' competing values and agendas for the sake of equity and social justice. Conclusions: The author concludes that the proximity to the evaluand and the integration of multiple perspectives in an evaluation represent two of evaluation's most enriching-rather than detrimental-factors. The author also asserts that a truly participatory approach can effectively coexist with advocacy, so long as evaluators are able to clarify their stances vis-à-vis the social, economic, and political issues associated with their evaluand.